GC-MS profiling and antifungal activities of Morinda citrifolia L. leaf extract against fungal pathogens of crown rot disease of banana - Haruna, Aishatu (Journal of Phytology, 2023)
The increasing demand for organic agricultural products especially among the elite stimulated the search for safe and alternative means of crown rot disease control. Morinda citrifolia is one of the listed medicinal plants among the Polynesian countries. This study documented the phytochemical profile of M. citrifolia using GC-MS and their antifungal activities against crown rot pathogens. The key phytochemical constituents of the extract were Phytol 2-Hexadecen-1-ol, (Diterpene) (25.96%), Squalene (Triterpene) (15.13%), 1, 3-Propanediol (Polyphenol) (4.68%), Pyran-4-one 4H-, 9 (Flavonoid), and 2H-1-Benzopyran-6-ol (Vitamins) (5.14%), 2-Cyclohexan-1-one, (Phenol) (2.54%). Fungal pathogens; Lasiodiplodia theobromae, Colletotrichum musae, Colletotrichum asianum and Fussarium Longipes isolated from crown rot infected banana fruits during earlier studies were used in this experiment. The poisoned food technique method was adopted in evaluating the inhibitory effect of the leaf extract against the fungal isolates. Results indicated significantly high fungal growth inhibition (P< 0.05) in concentration dependent manner on amended PDA media. 100% pathogen radial growth inhibition in all isolates was recorded at 100 mg/mL concentration. Therefore, findings of this study suggest application of leaf extract of M. citrifolia is a potential safe and alternative control of banana crown rot.